Myth in The Short Story "Haji Bangladesh" by Hasan Al-Banna: in Roland Baethes' Semiotics Study - Charolin, Mika; Nainggolan, Ledy Novwanty; Valiza, Intan; Harahap, Mesya Fadila Sani; Lubis, Delfira Almuharomah; Afarrel, Muhammad Ridho (Holistic Science, 2025)
This research aims to increase understanding of symbolism in Indonesian literature, especially in the short story "Haji Bangladesh" by Hasan Al Banna, through a semiotic theory approach. This analysis explores the signs and symbols in the story and their interactions in social, cultural and religious contexts. By using semiotic theory, it is hoped that narrative elements, characters and settings can be revealed that convey moral messages and critique the reality of society. The article entitled "Unpacking Symbolism: A Semiotic Approach in the Short Story 'Haji Bangladesh'" has academic and analytical benefits, and can increase readers' cultural awareness. The results and discussion section will explain the findings on symbolism and its contribution to the central theme of the short story. The conclusion will summarize the results of the analysis and provide recommendations for further research. Through Roland Barthes' semiotic study, this short story reveals the myth of the Hajj as a symbol of success and piety, and depicts the struggle of migrant workers. This approach allows in-depth analysis of the cultural symbols and social criticism contained in the narrative.